Management of urinary incontinence. Issue 2 (June 2020) - Nightingale, Gemma
Urinary incontinence is a common problem affecting 25–45% women. Effective management can have a huge impact on a patient's quality of life and many treatments are available. Management should be dictated by the degree of bother the symptoms are having, and vary depending on the type on incontinence. Conservative measures should always be initiated, including optimisation of body mass index and smoking cessation. Overactive bladder and urge urinary incontinence can be improved with bladder retraining and avoidance of bladder stimulants. Medical treatment then includes anticholinergic medications or Mirabegron. More invasive options include Botulinum Toxin A (Botox®) injections, sacral nerve stimulation or urological surgery. Stress urinary incontinence should be managed initially with pelvic floor exercises, and input from a specialist nurse or physiotherapist is beneficial. The surgical options for managing stress incontinence have changed considerably over the years, but include bladder neck injections, mid-urethral slings, colposuspension or autologous fascial slings. Mixed urinary incontinence is more challenging to manage, but all conservative measures should be started. Further treatment is directed towards the predominant symptom, but overactivity should be controlled before surgical measures for stress urinary incontinence are performed.